THE CURRENT METHODS FOR MOLECULAR DIAGNOSTICS OF FISH DISEASES (REVIEW) - Zaloilo, O.; Rud, Yu; Zaloilo, I.; Hrytsyniak, І. (Ribogospodarsʹka nauka Ukraïni, 2016)
Purpose. The methods of molecular diagnostic (MMD) gradually become widespread in modern fish farming. MMD contain a wide variety of specific approaches, each of which has distinct limits of their possible applications and is characterized by individual peculiarities in practical performance. In addition to high sensitivity and the possibility of rapid diagnostics, the main advantage of molecular methods is to determine the uncultivated infectious agents. DNA amplification allows identifying pathogenic microorganisms at very small quantities even in the minimum sample volume. Molecular methods of diagnostic enable the determination of infection in latent or acute phases. These methods allow showing the differences between pathogens with similar antigenic structures. The current literature data on this subject usually show a methodology in the narrow context of the tasks or practical results obtained through such approaches. Thus, a synthesis of existing information on the mechanisms of action and the limits of the typical problems of basic methods of molecular diagnostics are an urgent task of fish breeding. In particular, the following description will more effectively choose one or several approaches to identify pathogens in fish. Findings. This paper reviews the basic molecular methods that are used in the world's aquaculture for diagnosis of various diseases in commercial fish species. Originality. This work is a generalization of data on the principles and mechanisms for the implementation of diagnostics based on modern molecular techniques. For each of the mentioned approaches, the most promising areas of application were shown. The information is provided in the form of a comparative analysis of each methodology, indicating positive and negative practical aspects. Practical value. The current review of modern methods of molecular diagnostic in aquaculture is focused on practical application. Generalizing and analytical information can be used when planning the work flow and differential diagnostic measures (both operational as well and preventive), and will be useful when creating complex diagnostic approaches of general and individual character.